The Integration of Large Language Models in Financial Services: From Fraud Detection to Generative AI Applications - Snehansh Devera Konda, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the transformative impact of artificial intelligence in the financial services sector, focusing on the evolution from traditional applications to advanced AI systems. Through systematic analysis of implementation frameworks and regulatory considerations, this article demonstrates the sector's technological leadership, evidenced by a 56% higher AI implementation success rate compared to other industries. The article reveals how Large Language Models have revolutionized customer interactions, achieving 92% query resolution accuracy and 89% improvement in user engagement. Documentation and compliance processes have been transformed through AI automation, demonstrating an 82% improvement in real-time compliance monitoring and 89% enhancement in automated reporting accuracy. Financial institutions' established regulatory frameworks and mature governance structures have enabled superior technology integration, with an 82% cloud adoption rate and 85% risk management effectiveness. The article’s analysis of software development infrastructure shows significant advancement, with a 73% improvement in deployment frequency and 82% enhancement in code quality metrics. The article highlights how financial institutions' robust regulatory expertise provides a significant competitive advantage, demonstrated by 89% security compliance and 76% stronger compliance protocols. Drawing from comprehensive industry analyses and empirical evidence, this article contributes to the growing body of literature on AI implementation in regulated industries while providing practical insights for organizations balancing innovation with compliance requirements.
Keywords: Financial Technology (FinTech); Large Language Models (LLMs); Regulatory Compliance; Generative Artificial Intelligence; Banking Infrastructure Automation